Tregs: Where We Are and What Comes Next? - Zhao, Hai; Liao, Xuelian; Kang, Yan (Frontiers in Immunology, 2017)
Regulatory T cells are usually recognized as a specialized subset of CD4+ T cells functioning in establishment and maintanence of immune tolerance. Meanwhile, there is emerging evidence that Tregs are also present in various non-lymphoid tissues, and that they have unique phenotypes credited with activities distinct from regulatory function. Their development and function have been described in plenty of manuscripts in the last two decades. However, with the deepening of research in recent years, emerging evidence revealed some novel mechanisms about how Tregs exert their activities. Firstly, we discuss the expanding family of regulatory lymphocytes briefly and then, try to interpret how Foxp3 functions. Subsequently, another part of our focus is varieties of tissue Tregs. Next, we primarily discuss recent research on how Tregs work and their faceted functions in terms of soluble mediators, functional proteins and inhibitory receptors. In particular, unless otherwise noted, the term "Treg" is used here to refer specially to the "CD4+CD25+Foxp3+" regulatory cells.